The Influence of 1α.25-Dihydroxyvitamin D3 Coating on Implant Osseointegration in the Rabbit Tibia - Naito, Yoshihito (J Oral Maxillofac Res, 2014)
OBJECTIVES: This study aims to evaluate bone response to an implant surface modified by 1α,25-dihydroxyvitamin D3 [1.25-(OH)(2)D(3)] in vivo and the potential link between 1.25-(OH) 2D3 surface concentration and bone response. MATERIAL AND METHODS: Twenty-eight implants were divided into 4 groups (1 uncoated control, 3 groups coated with 1.25-(OH)(2)D(3) in concentrations of 10(-8), 10(-7) and 10(-6) M respectively), placed in the rabbit tibia for 6 weeks. Topographical analyses were carried out on coated and uncoated discs using interferometer and atomic-force-microscope (AFM). Twenty-eight implants were histologically observed (bone-to-implant-contact [BIC] and new-bone-area [NBA]). RESULTS: The results showed that the 1.25-(OH)(2)D(3) coated implants presented a tendency to osseointegrate better than the non-coated surfaces, the differences were not significant (P > 0.05). CONCLUSIONS: The effect of 1.25-(OH)(2)D(3) coating to implants suggested possible dose dependent effects, however no statistical differences could be found. It is thought that the base substrate topography (turned) could not sustain sufficient amount of 1.25-(OH)(2)D(3) enough to present significant biologic responses. Thus, development a base substrate that can sustain 1.25-(OH)(2)D(3) for a long period is necessary in future studies.